PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS DAN PENGHEMATAN PAJAK TERHADAP STRUKTUR MODAL - WAHYUNI, INDAH AYU TRIE; SURYANTINI, NI PUTU SANTI (E-Jurnal Manajemen, 2014)
Capital structure is a very important issue for companies because financial  capital is one of the driving factors in the company to be able to run the company operations. If determining the company’s capital structure false, it  will cause fixed costs become larger. Therefore, to know what is affecting capital structure is very important. Capital structure can be affected by several factors, among others is structure of assets, management attitude, tax, operating leverage, stability of sales, profitability, size, business risk. The aim of this research was to know the effect of size, profitability, and tax shields towards capital structure telecommunications companies in BEI . This research had 5 samples which choosen by census method. This research used multiple regression analysis. The result found that size and tax shields had  positive significant effect towards capital structure, meanwhile profitability had negative significant effect towards capital structure. Keywords: Size, Profitability, Tax shields, Capital Structure
Keywords: Size, Profitability, Tax shields, Capital Structure